2023
DOI: 10.1039/d3ob00225j
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents from Morus alba with proprotein convertase subtilisin/kexin type 9 expression and secretion inhibitory activity

Abstract: Six new flavanones, including sanggenol W (1), morusalnol D–F (2–4) and neovanone A–B (5–6), and fourteen known compounds were isolated from methanol extract of dried root bark of Morus alba...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Structural analysis of all isolated compounds was conducted according to the procedures outlined in our previous study for structural elucidation. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural analysis of all isolated compounds was conducted according to the procedures outlined in our previous study for structural elucidation. , …”
Section: Methodsmentioning
confidence: 99%
“…katsumadai extracts including diarylheptanoids, kavalactones, flavonoids, stilbenes, monoterpenes, sesquiterpenes, and triterpenes. Among these compounds, chalcones were found to prevent lipid accumulation, and acyclic triterpenoids were found to inhibit cholesterol acyl transferase activity. , As part of our ongoing study, , we conducted bioassay-guided isolation to identify compounds that have PCSK9 mRNA expression inhibitory activities. Based on in vitro experiments, it was found that the hexane-soluble fraction exhibited the highest activity.…”
Section: Introductionmentioning
confidence: 99%